2014
DOI: 10.3390/molecules190913147
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Nitrite-Scavenging Capacities of Phenolic Compounds from Sugarcane (Saccharum officinarum L.) Tops

Abstract: Sugarcane tops were extracted with 50% ethanol and fractionated by petroleum ether, ethyl acetate (EtOAc), and n-butyl alcohol successively. Eight phenolic compounds in EtOAc extracts were purified through silica gel and Sephadex LH-20 column chromatographies, and then identified by nuclear magnetic resonance and electrospray ionization mass spectra. The results showed that eight phenolic compounds from EtOAc extracts were identified as caffeic acid, cis-p-hydroxycinnamic acid, quercetin, apigenin, albanin A, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 31 publications
1
34
1
1
Order By: Relevance
“…3 However, under acid conditions, nitrite can be converted to nitrous acid, generating N 2 O 3 , which reacts with secondary amines to produce carcinogenic nitrosamines. 4,5 We also highlight that dietary nitrite, as also nitrate, can be positively associated to type 1 diabetes and cancer risk, 6,7 specifically to adult glioma and thyroid cancer risk. Xie et al 7 highlight that animal products are the main sources of dietary nitrite when compared with plant source products.…”
Section: Introductionmentioning
confidence: 82%
“…3 However, under acid conditions, nitrite can be converted to nitrous acid, generating N 2 O 3 , which reacts with secondary amines to produce carcinogenic nitrosamines. 4,5 We also highlight that dietary nitrite, as also nitrate, can be positively associated to type 1 diabetes and cancer risk, 6,7 specifically to adult glioma and thyroid cancer risk. Xie et al 7 highlight that animal products are the main sources of dietary nitrite when compared with plant source products.…”
Section: Introductionmentioning
confidence: 82%
“…Apigenin ( 41 ), characterized as 4′,5,7,-trihydroxyflavone is considered as a natural flavone, and rich in several fruits, vegetables and medicinal plants possessing numerous pharmacological potencies, such as anti-inflammatory, antioxidant, antibacterial, antiviral, antidiabetic, antidepressant, and anticancer activities, and the treatment of amnesia and Alzheimer’s disease, and insomnia [ 48 , 49 , 50 , 51 , 52 ]. SLH has been capable to isolate this natural product from hydroethanolic extracts of Brachychiton acerifolius leaf (eluent: methanol‒water 1:1) [ 34 ] and Saccharum officinarum sugarcane top (eluent: chloroform‒methanol 1:1) [ 53 ], ethyl acetate fractions of Chamaemelum nobile flowers (eluent: methanol‒dichloromethane 1:1) [ 38 ], and Solenostemon monostachys aerial part (eluent: n -hexane‒ethyl acetate 3:7, 2:8, 1:9; ethyl acetate; ethyl acetate‒methanol 1:9, 2:8, 4:6, 5:5) [ 39 ], n -butanol extract of xylem of Populus tomentosa (eluent: methanol‒water 1:1, 1:3) [ 41 ], and aqueous extract of Phlomis bruguieri aerial part (eluent: n -hexane‒methanol‒acetone 30:60:10) [ 40 ].…”
Section: Isolation Of Various Flavonoid Classifications By Sephadementioning
confidence: 99%
“…By subjecting hydroethanolic (50%) extract of sugarcane top part of Saccharum officinarum to various chromatographic methods, albanin A ( 84 ), australone A ( 85 ), and 5′-geranyl-5,7,2′,4′-tetrahydroxy-flavone ( 86 ) have been finally isolated by exploiting chloroform‒methanol (1:1) and pure methanol as eluting solvents in SLH column [ 53 ]. In another study, methanolic extract obtained from whole part of Dendrobium ellipsophyllum were subjected to SLH (eluent: acetone) and chrysoeriol ( 87 ) was consequently isolated [ 23 ].…”
Section: Isolation Of Various Flavonoid Classifications By Sephadementioning
confidence: 99%
“…This suggest that plant extract with antioxidant activity are able to prevent convulsion induced by aminophylline which is likely to be the mechanism of action of this extract as S. officinarum has been reported to possess antioxidant activity. 4,5 According to De Sarro et al, 31 pentylenetetrazol (PTZ) is suggested to exert its anticonvulsant effect by inhibiting the activity of gamma aminobutyric acid (GABA) at GABAA receptors. Gammaaminobutyric acid is the major inhibitory neurotransmitter which is implicated in epilepsy.…”
Section: Aminophylline-induced Convulsionmentioning
confidence: 99%
“…In folkloric medicine, it is used in the treatment of diarrhoea, dysentery, eyes, fever, arthritis, bedsores, boils, cancer, colds, cough, opacity, skin sores, sore throat, hiccups, inflammation, laryngitis, spleen, tumors, and wounds. 2 Biological activities reported on the leaf include antibacterial and anthelmintic, 3 anti-hyperglycaemic, antihyperlipidaemic, 4 antioxidant, 4,5 diuretic and antiurolithiatic 6 . Phytochemical screening of leaf extract of Saccharum officinarum reported the presence of glycosides, phytosterols, saponins, tannins, flavonoids.…”
Section: Introductionmentioning
confidence: 99%